Umiejętność odtwarzania hierarchii typu hiponimicznego przez niewidomych i widzących użytkowników języka - Mikołajczak-Matyja, Nawoja (Investigationes Linguisticae, 2006)
The ability to reconstruct hierarchical semantic structures by blind and sighted average language users. The present paper concerns the hierarchically organised semantic structure of the mental lexicon. The structure of hierarchical series of nouns constructed for 75 Polish nouns by 116 subjects (58 blind and 58 sighted) was analysed and compared.